Effects of Hemp Extract on Markers of Wellness, Stress Resilience, Recovery and Clinical Biomarkers of Safety in Overweight, But Otherwise Healthy Subjects. (2nd September 2020) - Lopez, Hector L.; Cesareo, Kyle R.; Raub, Betsy; Kedia, A. William; Sandrock, Jennifer E.; Kerksick, Chad M.; Ziegenfuss, Tim N.
Abstract: We determined the effects of a commercially available, GRAS (Generally Recognized As Safe) by independent conclusion, CBD-containing hemp oil extract on stress resilience, perceived recovery, mood, affect, body composition, and clinical safety markers in healthy human subjects. Methods: Using a randomized, placebo-controlled, double-blind design, 65 overweight, but otherwise healthy men and women (35.2 ± 11.4 years, 28.5 ± 3.3 kg/m 2 ) ingested either Hemp Oil Extract [Hemp, 60 mg/d PlusCBD TM Extra Strength Hemp Extract Oil (15 mg hemp-derived CBD)] or a placebo (PLA) every day for six weeks while continuing to follow their normal diet and physical activity patterns. Outcome variables included changes in stress resilience, a 14-item panel of various psychometric parameters, heart-rate variability, plasma chromogranin A, body composition, and general markers of health. Data were analyzed using mixed factorial ANOVA, t-tests with 95% confidence intervals, and effect sizes (ES). Results : HDL cholesterol significantly improved in the Hemp group ( p  = 0.004; ES = 0.75). No other statistically significant group x time interaction effects were observed. Statistical tendencies for between-group differences were found for 'I Get Pleasure From Life' ( p  = 0.06, ES = 0.48) and 'Ability to Cope with Stress' ( p  = 0.07, ES = 0.46). Sleep quality (Hemp, p  = 0.005, ES = 0.54) and sleep quantity (Hemp, p  = 0.01, ES = 0.58) exhibited significant within-group changes. All values for hepato-renal function, cardiovascular health, fasting blood lipids, and whole blood cell counts remained within normal clinical limits with no between-group differences over time being identified. Conclusions : Hemp supplementation improved HDL cholesterol, tended to support psychometric measures of perceived sleep, stress response, and perceived life pleasure and was well tolerated with no clinically relevant safety concerns. Registered at clinicaltrials.gov: NCT04294706.